Plants used in folk cosmetics and hygiene in the Arribes del Duero Natural Park (western Spain). - González, José Antonio; García-Barriuso, Mónica; Ramírez-Rodríguez, Rubén; Bernardos, Sonia; Amich, Francisco (Lazaroa, 2012)
In the present work we assess and document the ethnobotanical knowledge about cosmetic plants and plant species useful for personal and domestic hygiene in the Arribes del Duero Natural Park (provinces of Salamanca and Zamora, Spain). Field work was conducted between 2005 and 2009 by means semi-structured interviews and participant observation as well as transect walks in wild herbal plant collection areas, with 80 informants (mean age 72) in 18 localities. The informants, in particular the elderly women, are familiar with 32 useful plants distributed in 18 botanical families and know how to use them in a variety of ways. The most frequently used plants were Thymus mastichina (L.) L. and Quercus ilex subsp. ballota (Desf.) Samp. Different plant parts are used, but the branches are exploited more frequently. The uses documented are of great ecological value since the products obtained are less harmful to our health and the environment.